Comparison of Dacron Band versus Segmental Annuloplastyin Treatment of Tricuspid Valve Repair - Asif Hassan, Saira Gul, Wasim Riaz, Shahnoor Aziz, Bahar Ali, Farhan Ejaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to compare outcome of Dacron Band versus Segmental Annuloplasty in treatment of TV repair. Study Design: This was a randomized controlled trial. Place and Duration: This study was conducted at the Cardiac surgery Department, PIC, Jail Road, Lahore from 25 October 2021 to 25 Oct, 2022. Methodology:A total of 148 patients were enrolled in this study and divided into two groups equally. For categorical data like gender, and grades of Tricuspid regurgitation, frequency and percentages was used. For quantitative data mean ± S.D was computed. P-value ≤ 0.05 was taken as significant. Results: The mean age of the cases in Group-A was 47.97 ± 8.29 and in Group-B was 51.01 ± 7.78. In our study post-operative RVEDD and TVPG found significant with p-value 0.044 and <0.01 respectively. Similarly, the p-value of follow-up RVSTDI and RVEDD was statistically significant with p-value 0.03 and 0.007 respectively. Conclusion: Both Dacron band and segmental annuloplasty techniques are available for TV repair; however, dacron band placement in TV repair patients is associated with better RV remodelling, and as a result, a more likely improvement in right ventricular function and a better repair outcome are predicted. After tricuspid valve surgery, dacron band implantation is correlated with a lower incidence of TR recurrence and enhanced long-term event-free survival. As a result, this method in tricuspid valve surgery should be used more frequently. Keywords: Segmental Annuloplasty, Dacron Band, TR, TV repair